ACKR3 promotes CXCL12/CXCR4-mediated cell-to-cell-induced lymphoma migration through LTB4 production - Antonello, Paola; Pizzagalli, Diego U.; Foglierini, Mathilde; Melgrati, Serena; Radice, Egle; Thelen, Sylvia; Thelen, Marcus (Frontiers in Immunology, 2023)
Chemotaxis is an essential physiological process, often harnessed by tumors for metastasis. CXCR4, its ligand CXCL12 and the atypical receptor ACKR3 are overexpressed in many human cancers. Interfering with this axis by ACKR3 deletion impairs lymphoma cell migration towards CXCL12. Here, we propose a model of how ACKR3 controls the migration of the diffused large B-cell lymphoma VAL cells in vitro and in vivo in response to CXCL12. VAL cells expressing full-length ACKR3, but not a truncated version missing the C-terminus, can support the migration of VAL cells lacking ACKR3 (VAL-ko) when allowed to migrate together. This migration of VAL-ko cells is pertussis toxin-sensitive suggesting the involvement of a Gi-protein coupled receptor. RNAseq analysis indicate the expression of chemotaxis-mediating LTB4 receptors in VAL cells. We found that LTB4 acts synergistically with CXCL12 in stimulating the migration of VAL cells. Pharmacologic or genetic inhibition of BLT1R markedly reduces chemotaxis towards CXCL12 suggesting that LTB4 enhances in a contact-independent manner the migration of lymphoma cells. The results unveil a novel mechanism of cell-to-cell-induced migration of lymphoma.